THE STRATEGY OF FEATURING THE GAME HONOR OF KINGS THROUGH CHARACTERIZATION IN THE DRAMA SERIES YOU ARE MY GLORY (2021) - Homario, Bella; Wulandari, Adi Kristina (International Review of Humanities Studies, 2024)
The drama series You Are My Glory (Nǐ shì wǒ de róngyào你是我的荣耀), directed by Wang Zhi (王之), aired in 2021 and consists of 32 episodes. This research focuses on the first 14 episodes, which showcase the popularity of the game Honor of Kings-HoK (Wángzhě róngyào王者荣耀) through the interactions and dialogue between the two main characters, Yu Tu (于途) and Qiao Jingjing (乔晶晶). The integration of the popular online game HoK with the drama, starring top actors and actresses, represents a novel strategy that warrants further study. The analysis is conducted intrinsically by examining the characterizations of the two main characters in You Are My Glory and extrinsically by describing the social realities of urban Chinese society. This research finds that the portrayal of the HoK game's popularity through the interactions and dialogue between the main characters reflects contemporary conditions in China. Key findings include: the online game HoK is immensely popular among young urban Chinese; the game's popularity illustrates the advancement of information technology in China; Depicting the popularity of HoK through character interactions is a strategic element contributing to the success of the drama series You Are My Glory. This strategy of combining the online game HoK with the drama series aligns with the core goals of the Two Centenaries (Liǎng gè yībǎi nián 两个一百年) and the themes in Xi Jinping's speeches. It represents a new approach by China to bolster local cultural development and extend its soft cultural power globally.